Exploring supply chain capabilities as drivers for willingness to adopt blockchain technology using a technology–organization–environment (TOE) framework - Hsu, Sara; Gligor, David; Garg, Vipul; Gölgeci, Ismail; Choi, Rak-Joon (Taylor & Francis, 2025)
As blockchain technology reshapes operations and supply chain management (OSCM), understanding its capability-driven adoption pathways is crucial for enhancing supply chain efficiency, resilience, and decision-making. This study applies Fuzzy-Set Qualitative Comparative Analysis (fsQCA) within the Technology-Organisation-Environment (TOE) framework to analyse data from supply chain managers with blockchain implementation experience. Our findings reveal three adoption pathways: (1) Dynamic Collaborators, who integrate blockchain through external collaboration and agility; (2) Resilient Specialists, who prioritise internal resilience over partnerships; and (3) Proficient Collaborators, who emphasise information sharing and agility without deep IT integration. These results highlight the causal complexity of blockchain adoption, demonstrating that firms follow multiple strategic configurations based on their capability portfolios. By uncovering scalable, context-specific adoption pathways, this study provides actionable insights for managers and policymakers, advancing both blockchain integration strategies and the broader OSCM literature.
Keywords: Blockchain; supply chain capabilities; fsQCA; agility; resilience; TOE; blockchains